2018
DOI: 10.1002/anie.201801361
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Methods and Design Principles for Cell‐Penetrant Peptides

Abstract: Biomolecules such as antibodies, proteins, and peptides are important tools for chemical biology and leads for drug development. They have been used to inhibit a variety of extracellular proteins, but accessing intracellular proteins has been much more challenging. In this review, we discuss diverse chemical approaches that have yielded cell-penetrant peptides and identify three distinct strategies: masking backbone amides, guanidinium group patterning, and amphipathic patterning. We summarize a growing number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 197 publications
(433 reference statements)
1
131
0
Order By: Relevance
“…There is compelling evidence that this journey often involves endocytosis (75,76), the natural cellular process by which extracellular material is taken up into vesicles formed from the plasma membrane. However, the pathway into the cytosol requires not just uptake into endocytic vesicles, but also endosomal release, and this second step is widely recognized as the bottleneck hindering the efficient delivery of peptidic materials into the cytosol and nucleus (11,(77)(78)(79)(80)(81)(82)(83)(84)(85). We discovered several years ago that CPMPs, such as ZF5.3 (11,86,87), overcome this bottleneck to reach the cytosol with exceptional efficiency, both with (16) and without (12) an appended protein cargo.…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that this journey often involves endocytosis (75,76), the natural cellular process by which extracellular material is taken up into vesicles formed from the plasma membrane. However, the pathway into the cytosol requires not just uptake into endocytic vesicles, but also endosomal release, and this second step is widely recognized as the bottleneck hindering the efficient delivery of peptidic materials into the cytosol and nucleus (11,(77)(78)(79)(80)(81)(82)(83)(84)(85). We discovered several years ago that CPMPs, such as ZF5.3 (11,86,87), overcome this bottleneck to reach the cytosol with exceptional efficiency, both with (16) and without (12) an appended protein cargo.…”
Section: Discussionmentioning
confidence: 99%
“…Several assays have been developed to measure the cell penetration of biomolecules, which we recently reviewed. 11 Most commonly, molecules are tagged with a fluorescent dye and tracked using fluorescence or confocal fluorescence microscopy, 12,13 but these methods cannot unambiguously quantitate localization to cytosolic and endosomal compartments. Alternatives have been developed that address some of these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatives have been developed that address some of these drawbacks. 11,1417 Still, there remains a need for compartment-specific, quantitative and high-throughput assays for measuring the cell penetration of biomolecules of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The results reported herein highlight the potential of the glycosylationo fp enetratingp eptides to modulatetheir activity. [17][18][19][20][21][22][23][24][25] Interesting penetrating properties were further discovered in different naturala nd artificial structures, such as polyprolines, [26] guanidinyl glycosides, [27,28] b-peptides, [29] peptiden ucleic acids (PNAs), [30] nonpeptidic guanidinylated dendritic structures, [31] self-assembled nanofibers, [32,33] synthetic polymers, [34][35][36][37] supramolecular structures, [38][39][40] and polydisulfides. [14] These studies also showed that oligolysines were less effective than that of the oligoarginines analogues, [15] and triggered the development of synthetic penetrating oligoarginines.…”
Section: Introductionmentioning
confidence: 99%